IT Sector in Poland — Opportunity for Enterprise Development - Szajt, M. (Электронное моделирование, 2009)
The study contains the analysis of IT sector. The author describes the situation of this sector in Poland and other European countries by indicating development opportunities and potential barriers. In the research part a linear equation model, which indicates the relation between broadband access and total turnover, was applied. Проведен анализ сектора информационных технологий. Описано состояние этого сектора в Польше и других европейских странах относительно возможностей развития и потенциальных барьеров. Использована линейная модель, устанавливающая соотношение между широким доступом и общим товарооборотом. Наведено аналіз сектора інформаційних технологій. Описано стан цього сектора у Польщі та інших європейських країнах відносно можливостей розвитку і потенційних бар’єрів. Використано лінійну модель, що встановлює співвідношення між широким доступом та загальним товарообігом.